Análisis morfodinámico y estimación de la erosión hídrica del complejo volcánico de La Primavera, Jalisco - Guzmán Cervantes, Consuelo Selene (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
The La Primavera Volcanic Complex (CVLP) is a natural area of flora and fauna protection with an approximate age of 95 thousand years that has a great diversity of geoforms, product of the coexistence of both internal and external geological processes, as well as anthropic processes. The morphodynamic processes within the CVLP are associated with water erosion, transport and sedimentation of geological material. These processes include mass removal, fluvial deposition, alluvial-colluvial deposition, hydrothermal alteration, and banks of extractive material, although the predominant process is laminar and concentrated water erosion. Ignorance of the dynamics, distribution, categorization and quantitative estimation of these processes when implementing projects and activities within the CVLP puts its ecological balance at risk. This study shows a detailed cartographic analysis of the morphodynamic processes within the CVLP, as well as the quantitative estimation of water erosion per volcanic unit in an actual and a potential scenario using the RUSLE equation. The morphodynamic analysis revealed a high density of gullies with diverse drainage patterns, product of concentrated or fluvial erosion and a tectonic-structural control, developing mainly in the volcanic units composed of volcano-lacustrine sediments and pyroclastic flows. A total of 480 flow-type and 6 avalanche-type mass removal processes, 17 extractive banks of stone material, 11 geothermal well platforms, and at least 15 hydrothermal alteration zones were mapped. Regarding water erosion, the actual scenario reported values ranging from 0 to ⁓250 t/ha*year, with normal and light erosion predominating in 78.81% of the area. The potential scenario reported values from 0 to ⁓2100 t/ha*year, with catastrophic and severe type erosion predominating in more than 90% of the surface area. The results of this study show the diversity of morphodynamic processes, geoforms and anthropic agents that make the CVLP particularly fragile in the conservation of its soils.

El Complejo Volcánico de La Primavera (CVLP) es un área natural que cuenta con una gran diversidad de geoformas, producto de la coexistencia tanto de procesos geológicos internos y externos, así como de procesos antrópicos. Los procesos morfodinámicos dentro del CVLP están asociados a la erosión hídrica, transporte y sedimentación de material geológico. Dentro de estos procesos se encuentran los procesos de remoción en masa, deposición fluvial, deposición aluvial-coluvial, alteración hidrotermal, bancos de material extractivo, aunque el proceso predominante es la erosión hídrica laminar y concentrada. En este estudio se muestra un análisis cartográfico detallado de los procesos morfodinámicos dentro del CVLP, así como la estimación cuantitativa de la erosión hídrica por unidad volcánica en un escenario real y uno potencial mediante el uso de la ecuación RUSLE. El análisis morfodinámico reveló una alta densidad de barrancas con patrones de drenaje diverso, producto de la erosión concentrada o fluvial y un control tectónico-estructural, desarrollándose principalmente en las unidades volcánicas compuestas por sedimentos vulcano-lacustres y flujos piroclásticos. Se cartografiaron 480 procesos de remoción en masa de tipo flujo y 6 de tipo avalancha, 17 bancos extractivos de material pétreo, 11 plataformas de pozos geotérmicos, y al menos 15 zonas de alteración hidrotermal. En cuanto a la erosión hídrica, el modelo reportó valores que van de 0 a ⁓250 t/ha*año, predominando la erosión de tipo normal y ligera en un 78.81% de la superficie. El escenario potencial reportó valores desde 0 hasta ⁓2100 t/ha*año, predominando la erosión de tipo catastrófica y severa en más del 90% de la superficie. Los resultados de este estudio muestran la diversidad de procesos morfodinámicos, geoformas y agentes antrópicos que hacen que el CVLP tenga una fragilidad particular en la conservación de sus suelos.
Instituto de Investigaciones en Ciencias de la Tierra. Maestría en Geociencias y Planificación del Territorio
Keywords: info:eu-repo/classification/cti/1; INICIT-M-2024-0190; Geomorfología volcánica; Pérdida de suelo; Procesos exógenos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18583